Studies in law, politics, and society. - Sarat, Austin (Studies in law, politics, and society., 2020)
This volume of Studies in Law, Politics and Society brings together an international and interdisciplinary array of scholars to explore issues on the cutting edge of socio-legal research. They consider the complex connections of liberal democracy, human rights, governance in and through courts, the challenges terrorism poses to criminal law, and the problematics of global governance. Taken together, the chapters in this volume point to exciting new directions for legal scholars.